Editorial: Narrative - Interdisciplinary Perspectives - Irmina Rostek (Jesuit University Ignatianum in Krakow, 2018)
Ladies and Gentlemen, Philosophers have been reflecting on the concept of narration since the ancient times, and the concept has played a prominent role in the studies of human existence and its meaning. Roland Barthes (1966) stated, that the narrative is present at all times, in all places, in all societies -   in myths, legends, fairy tales, novels, dramas, movies, comics, conversations ...